PENERAPAN METODE EKSPERIMEN PADA MATA PELAJARAN IPA KELAS V DI MI MUHAMMADIYAH KRAJAN KECAMATAN PEKUNCEN KABUPATEN BANYUMAS TAHUN PELAJARAN 2016/2017 - Cahaya Ramadanti, Ewita (Penerbit CV Tentrem Karya Nusa, 2019)
Learning method is teacher how the teacher is used by teacher in delivering learning massages to students in achieving learning goals. The teacher must be able to choose the right method that is adapted to the subject metter so that the learning objectives can be achieved. This is the background of this thesis. One of them using the experimental method. The learning process emphasizes providing direct experience to develop competencies in order to explore andunderstand the natural environment scientifically. This type of research is descriptive qualitative research in which reseaechers go directly to the location of research to obtain data and information about the application of experimental methods in class V science subjects of MI Muhammadiyah Krajan Pekuncen District Banyumas Recency 2016/2017 academic year.. The results of this study indicate that the implementation of the experimental method in science subjects at MI Muhammadiyah Krajan in the science learning process was good because the experiment had an impact on students providing direct experience to develop competencies, active students anda explore and understand science scientifically. This is considered appropriate to be learned in classV on the cubjects of the characteristics of light.Key Words: Method, Experimental Method, Science classes,